Improving Student Success in Calculus at Seattle University. Issue 2 (7th February 2016) - Carter, J. D.; Helliwell, D.; Henrich, Allison; Principe, M.; Sloughter, J. M.
Abstract: Finding ways to improve student success in calculus is a critically important step on the path to supporting students who are pursuing degrees in STEM fields. Far too many students fail calculus 1 and are pushed to drop their majors in technical fields. One way of addressing this issue is by following a program that was pioneered at University of Colorado Boulder. At Boulder, oral exam reviews are offered to mathematics students in conjunction with other support. Oral reviews are structured, ungraded, optional, collaborative review sessions that prepare students to take exams by improving their understanding of mathematical concepts. In this paper, we discuss how we have implemented the University of Colorado Boulder model at Seattle University, and we report on the successes and the challenges of the program.